Fase Pendidikan Islam Anak-Anak dalam Perspektif Fikih - Mukhlas, Abdulloh Arif (Jurnal Pendidikan Agama Islam Miazhar, 2025)
Education should not be ignored by humans. The innate sense that God gives is the main capital for education and is what differentiates humans from other creatures. Choosing the right education is also no less important. Because the wrong choice in providing education to children will affect their future. Education during childhood is the foundation for character formation. The developmental phases in children's growth require the concept of education for children to also experience different phases. This research seeks answers about the phases of children's education from a fiqh perspective. Using descriptive qualitative research methods, the data sources used in this research are the Al Quran, hadith, book references and journals that discuss the stages and development of children in education. The results of this research are that children's developmental phases are grouped into three which have different educational demands. The first phase is shobiy, followed by the mumayyiz phase and then the murohiq phase.